Fable of the free beast: poetry, sexuality and procreation in Trilce. A new hypothesis about the name - Mazzotti, José Antonio (2022)
Based on various poems from Trilce (1922), this article explores some of the instances in which the sexual theme is present in the second book by César Vallejo, and proposes a new hypothesis about the origin and meaning of the neologism «Trilce» based on the relationship between eroticism and procreation. The poet’s tendency towards erotic themes is evident from Los heraldos negros, but the exacerbation of sexuality directly alluded to in Trilce is one of the marks that differentiate it from his previous work, turning it into a sample of moral and aesthetic avantgarde that in part explains the rejection with which the book was received in the Peruvian cultural environment. Added to this is the constant recurrence of frustrated procreation (abortion) that underlies one of the main semantic fields of the work.